ANALISIS KEMAMPUAN PENALARAN MATEMATIK SISWA SMP PADA MATERI SEGIEMPAT DAN SEGITIGA - Yuni Aprilianti; Luvy Sylviana Zanthy (Journal on Education, 2019)
One aspect that must be mastered by students to achieve the goal of mathematics learning is mathematical reasoning ability. In other words, students are able to use mathematics as a reasoning tool both in mathematics learning in the classroom and in everyday life. This study aims to describe junior high school students' mathematical reasoning abilities in understanding quadrilateral and triangle material. This type of research is a qualitative descriptive study with 20 students of grade VIII junior high school students. The research data is in the form of written answers obtained from written tests in the form of descriptions. The results of this study are based on the results of descriptions and interviews of several students, namely for reasoning ability with written text 20% indicator (low), mathematical expression 15% (quite low), drawing 13% (very low) while for learning interest, as much as 5% have interest is very high, as many as 20% have high interest, as much as 25% have enough interest, as much as 50% have low interest. So that it can be concluded that the level of reasoning ability of students' learning interests is still low.